THE EFFECT OF ELECTRONIC WORD OF MOUTH (E-WOM), PRICE AND PRODUCT QUALITY ON THE PURCHASE DECISION OF URBAN LIP CREAM MATTE IMPLORA PRODUCTS AMONG UNIVERSITAS MALIKUSSALEH STUDENTS - Fidya Amira Nasution; Khairina AR; Jullimursyida; Rahmaniar (RADJA PUBLIKA, 2025)
This study aims to determine the effect of electronic word of mouth (ewom), price and product quality on purchasing decisions for Implora matte urban lip cream products among students of the Faculty of Economics and Business at Universitas Malikussaleh. The research method used by this study is a quantitative method with multiple linear regression analysis techniques. The population in this study were all active students of the Faculty of Economics and Business at Universitas Malikussaleh totaling 3426 students. To obtain a sample that can represent the population, the Hair formula was used in determining the sample. The number of respondents obtained was 110 respondents. The results of this study indicate that electronic word of mouth has no significant effect, while price and product quality significantly influence purchasing decisions for Implora matte urban lip cream products.